Emergence of Daptomycin-Resistant VRE: Experience of a Single Institution - Kamboj, Mini (2011)
Recent surveillance from US hospitals shows that more than 99.5% of vancomycin-resistant enterococci (VRE) isolates remain susceptible to daptomycin. This report describes emergence of daptomycin-resistant VRE at a major cancer center. The percentage of patients with daptomycin-resistant VRE bacteremia increased from 3.4% in 2007 to 15.2% in 2009 (P = .03). Without susceptibility data, empiric daptomycin therapy for VRE infections should be used with caution.